2015
DOI: 10.1016/j.celrep.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Co-repressor Function of the Hippo Pathway Transducers YAP and TAZ

Abstract: YAP (yes-associated protein) and TAZ are oncogenic transcriptional co-activators downstream of the Hippo tumor-suppressor pathway. However, whether YAP and/or TAZ (YAP/TAZ) engage in transcriptional co-repression remains relatively unexplored. Here, we directly demonstrated that YAP/TAZ represses numerous target genes, including tumor-suppressor genes such as DDIT4 (DNA-damage-inducible transcript 4) and Trail (TNF-related apoptosis-inducing ligand). Mechanistically, the repressor function of YAP/TAZ requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
230
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(259 citation statements)
references
References 43 publications
19
230
1
3
Order By: Relevance
“…Many studies to data have focused on identifying genes upregulated by YAP/TAZ [22]. Here, we unequivocally demonstrate that YAP is a repressor of S100A7 induction via the Hippo pathway in A431 cells.…”
Section: Introductionsupporting
confidence: 50%
“…Many studies to data have focused on identifying genes upregulated by YAP/TAZ [22]. Here, we unequivocally demonstrate that YAP is a repressor of S100A7 induction via the Hippo pathway in A431 cells.…”
Section: Introductionsupporting
confidence: 50%
“…Recent studies demonstrated that YAP can function as a transcription repressor through recruitment of the NuRD complex in certain genomic regions (Beyer et al, 2013; Kim et al, 2015). It prompted us to examine whether YAP may directly repress Myocd transcription in the context of smooth muscle cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…It will be interesting to learn whether the same mechanism holds true for other YAP/TAZ-utilized TFs. In some instances YAP/TAZ also operate as transcriptional corepressors for additional target genes [43,79,80]. Intriguingly this nuclear function also requires TEAD TFs [43,80].…”
Section: Nuclear Functions Of Yap and Tazmentioning
confidence: 99%